Joining carbon nanotubes - G. Seth Roberts (2018)
To fully exploit the exceptional electronic and mechanical properties of carbon nanotubes in real-world applications, it is desirable to create carbon nanotube networks in which separate, multiple nanotubes are joined so that as many as possible of the properties of single nanotubes are conserved. In this review we summarize the progress made towards this goal, covering techniques including electron and ion beam irradiation, Joule heating and spark plasma sintering. © 2011 The Royal Society of Chemistry.